Souvenirs of Madame Vigée Le Brun, Volume 1 - Vigée-Lebrun, Louise-Elisabeth 1755-1842 (Cambridge library collection. Art and architecture, 2016)
The most accomplished female painter of her age, Élisabeth Vigée-Lebrun (1755–1842) is best remembered for her many portraits of Queen Marie Antoinette of France. Her two-volume autobiography was published in France in 1835–7, and this English version (of which the translator is unknown) in 1879. It begins with a series of ten letters to a Russian friend, Princess Kourakin, describing her family and early life, her artistic training, and her rise to the position of portraitist to the queen. The letters end with the Revolution and Vigée-Lebrun's flight abroad: the 'souvenirs' which follow describe her years of exile and her eventual return to France. Throughout her life, she supported herself and her family by her painting. Volume 1 ends with her staying in Austria, after a tour of the cities of Italy, during which she studied art as well as participating in the life of high society